KINERJA PEGAWAI KELURAHAN DALAM PELAYANAN MASYARAKAT DI KELURAHAN TAMALANREA KECAMATAN TAMALANREA KOTA MAKASSAR - Taufan Alwany (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2018)
Community service has become a mission that must be implemented and improved in order to create good governance. It is expected that services carried out by government organizations in the regions in order to meet the increasingly complex needs of the community can work well. The performance of employees of the Tamalanrea Village in realizing services for the community has not yet been fully implemented optimally, there are still obstacles in the process of implementing services in the Tamalanrea Village, such as; the lack of supporting facilities and infrastructure in the process of service to the community, low awareness of employees about their duties and responsibilities as public servants, and the mindset of the people who want instant service so as to lead to brokering in the licensing process in Tamalanrea Sub-District